Genetic diversity analysis in Brassica varieties through RAPD markers - Ghosh, KK; Haque, ME; Parvin, S; Akhter, F; Rahim, MM (Bangladesh Journal of Agricultural Research, 2009)
This investigation was aimed at exploring the genetic diversity and relationship among nine Brassica varieties, namely BARI Sharisha-12, Agrani, Sampad, BINA Sharisha-4, BINA Sharisha-5, BARI Sharisha-13, Daulot, Rai-5, Alboglabra using Random Amplified Polymorphic DNA (RAPD) markers. In total, 59 reproducible DNA bands were generated by four arbitrary selected primers of which 58 (98.03%) bands were proved to be polymorphic. These bands ranged from 212 to 30686 bp in size. The highest proportion of polymorphic loci and gene diversity values were 37.29% and 0.1373, respectively, for BARI Sharisha-12 and the lowest proportion of polymorphic loci and gene diversity values were 8.47% and 0.0318, 8.47% and 0.0382 for BINA Sharisha-4 and Rai-5, respectively. A dendrogram was constructed using unweighted pair group method of arithmetic mean (UPGMA). The result of cluster analysis indicated that the 9 accessions were capable of being classified into 2 major groups. One group consists of BARI Sharisha-12, Agrani, Sampad, Daulot, Rai-5, Alboglabra. where Daulot and Rai-5 showed the lowest genetic distance of 0.049. And another group contains BINA Sharisha-4, BINA Sharisha-5, and BARI Sharisha-1 3, where BINA Sharisha-5 and BARI sharisha-13 showed genetic distance of 0.071. Key Words: RAPD, Brassica, genetic distance, polymorphic band. DOI: 10.3329/bjar.v34i3.3976 Bangladesh J. Agril. Res. 34(3) : 493-5032, September 2009